Antibiotics: Indications and Modifications in Seriously Ill Patients (Revista de Medicina Clinica, 2021)
Background. ICU is especially important for the type of patients and treatments, specifically with the use of antibiotics. Objective. To quantify the use and modification of antibiotics in ICU. Patients and Methods. In a prospective observational study, 32 patients were selected with the inclusion criteria: a)> 6 days in ICU, b) receiving parenteral antimicrobial, c) probability of death> 40% by APACHE IV. Quantifying the empirical antimicrobial, microbiological cultures and microbiological antibiotics in both stages. Results. 187 uses antibiotics were quantified; 73 (39%) 2.5 X empirical antibiotic / patient and duration of 1 to 3 days in 80% of cases. Bacteriological group accounted for 114 (61%) use of antibiotics; X 4 with antibiotics / patient and duration of 1 and 32 days; crops corresponded to 20 different bacteria, found in 25% Pseudomonas aeruginosa; 18.75%  Escherichia coli and Klebsiella pneumoniae respectively, and 15.6% Staphylococcus aureus. Empirical antibiotic commonly used: carbapenemes, cephalosporin and quinolones in 40.6% respectively. Of "microbiological" antibiotics, carbapenemes in 87.5% of cases; quinolones, beta-lactams and aminoglucosides in 43.7% respectively. 732 days of stay joined with X of 22 days /patient Conclusions. empirical antimicrobial modified in 40% of cases, with X 1 to 3 days of use, unlike that used microbiological averaging 7 days. Five of the six pathogens resistant to multiple antimicrobial agents frequently found in ICU.
Keywords: empirical antibiotics; microbiological antibiotics